A computational model of the effect of capillary density variability on oxygen transport, glucose uptake, and insulin sensitivity in prediabetes. (February 2017) - Sové, Richard J.; Goldman, Daniel; Fraser, Graham M.
Abstract: Objectives: The purpose of this study was to model how CD variability affects tissue oxygenation under resting and exercise conditions. Additionally, we examine how CD impacts glucose and insulin transport in skeletal muscle. Methods: We applied an established 3D finite difference model of oxygen transport to predict tissue oxygenation using FCD, hemodynamics, and SO2 measurements from a previous study. A 2D finite element model of glucose transport was applied to predict glucose and insulin uptake in PP and fasting conditions using the same range of CD. Results: Control simulations used CD ranging from 562.5 to 781.3 capillaries/mm 2, whereas prediabetic densities ranged from 375.0 to 593.8 capillaries/mm 2 . Mean tissue PO2 was 30.6±4.6 to 40.5±3.6 mm Hg for rest and 19.6±6.7 to 33.27±4.7 mm Hg for control and prediabetic simulations, respectively. Mean PP glucose concentrations were 5.85±1.13 mmol/L in the control group and 5.11±1.28 in the prediabetic simulations. Glucose uptake rates were 35% lower in the lowest capillary CD case compared to the high CD simulation. Conclusions: Our simulations predict that CD decreases can have a substantial effect on oxygen delivery and glucose disposal across the observed physiological ranges of capillarization.